A layered Mn-based coordination polymer as an efficient heterogeneous catalyst for CO2 cycloaddition under mild conditions. Issue 25 (14th June 2022) - Zhou, Shi; Yan, Guosong; Gao, Baihui; Jiang, Wei; Liu, Bo; Zhou, Tianyu; Liu, Chunbo; Che, Guangbo
Abstract : A layered coordination polymer has been constructed by using a semi-rigid ligand, exhibiting a robust catalytic activity toward the cycloaddition of CO2 with epoxides. Abstract : The cycloaddition of carbon dioxide into value-added chemicals is of great significance to reduce carbon emission. Herein, a Mn-based coordination polymer [(CH3 )2 NH2 ]2 n [Mn3 (L)2 ] n · n DMF·0.5 n H2 O (JLNU-104 ) has been constructed by the solvothermal reaction of 1, 2, 4, 5-tetrakis[(4-carboxy)phenoxymethyl]benzene (H4 L) with MnCl2 . JLNU-104 is a 2D layered complex assembled with infinite Mn-carboxylate chains and semi-rigid L 4− ligands. Moreover, the layered structures can be held together through C–H⋯π interactions to form a 3D supramolecular architecture. Thanks to the rich Lewis acid sites, JLNU-104 exhibits durable catalytic performance for the cycloaddition of CO2 with epoxides. This work provides an insight into the design of functional crystalline catalysts for energy conversion.